Transcriptome atlas of Striga germination: Implications for managing an intractable parasitic plant - Gilles Irafasha; Sylvia Mutinda; Fredrick Mobegi; Brett Hale; George Omwenga; Asela J. Wijeratne; Susann Wicke; Emily S. Bellis; Steven Runo (Plants, People, Planet)
Societal Impact Statement Witchweeds, parasitic plants of the genus Striga, are nicknamed “cereal killers” because of their devastating destruction of Africa's most staple cereals, including maize, sorghum, millets, and upland rice. The parasite relies on biomolecules emitted from the host roots to germinate and therefore initiate its infectious lifecycle. Some sorghum varieties have evolved to not produce effective germination stimulants, making them resistant to the parasite. Here, the genetic factors that underpin Striga germination were assessed, followed by a discussion of how such knowledge can be used to develop new Striga management strategies through the disruption of host–parasite communication exchange. Summary Seeds of the parasitic plant Striga are dormant. They only germinate in response to biomolecules emitted from the host's root exudate, strigolactones (SL). But it is now emerging that Striga germination is a much more complex process regulated by crosstalk of hormone signaling pathways. To further understand the genetic basis of the communication exchange between Striga and its host sorghum, we performed a comparative transcriptomic analysis. We sought to identify major transcriptomic changes that define the germination process in Striga and a set of genes that may contribute to the differences in germination rates. Results showed that germination proceeds immediately after SL perception and is marked by a wave of transcriptional reprogramming to allow for metabolic processes of energy mobilization. Cluster analysis using self‐organizing maps revealed a time‐phased and genotype‐differentiated response to germination stimulation. The variation in germination was also a function of hormonal crosstalk. The early germination stage was associated with significant repression of genes in the abscisic acid (ABA) biosynthesis pathway. Other hormones influenced germination as follows: (i) ABA and auxin repressed germination; (ii) brassinosteroid, ethylene, and jasmonic acid promoted germination; and (iii) cytokinin had a more prominent role post‐germination rather than during germination. Perception of SL sets the germination program leading to different rates of germination in sorghum, followed by a complex hormonal regulation network that acts to either repress or enhance germination. We discuss the implications of these findings and present new plausible Striga management strategies.